2020
DOI: 10.1101/2020.02.08.939892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell Analysis of ACE2 Expression in Human Kidneys and Bladders Reveals a Potential Route of 2019-nCoV Infection

Abstract: Since December 2019, a novel coronavirus named 2019 coronavirus (2019-nCoV) has emerged in Wuhan of China and spread to several countries worldwide within just one month.Apart from fever and respiratory complications, acute kidney injury has been observed in some patients with 2019-nCoV. In a short period of time, angiotensin converting enzyme II (ACE2), have been proposed to serve as the receptor for the entry of 2019-nCoV, which is the same for severe acute respiratory syndrome coronavirus (SARS). To investi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 23 publications
6
44
0
1
Order By: Relevance
“…First, ACE2 was found highly expressed in intestine, kidney, gallbladder, adrenal gland, testis, and seminal vesicle among 61 organs in the HPA, at both the protein and RNA levels ( Figure S1), consistenting with previous reports [13,14]. Single-cell sequencing also showed that ACE2 was expressed in only amounts in airway tissue and type II alveolar cells (AT2).…”
Section: Expression Of Virus-associated Proteins On Epithelial Cells supporting
confidence: 89%
See 1 more Smart Citation
“…First, ACE2 was found highly expressed in intestine, kidney, gallbladder, adrenal gland, testis, and seminal vesicle among 61 organs in the HPA, at both the protein and RNA levels ( Figure S1), consistenting with previous reports [13,14]. Single-cell sequencing also showed that ACE2 was expressed in only amounts in airway tissue and type II alveolar cells (AT2).…”
Section: Expression Of Virus-associated Proteins On Epithelial Cells supporting
confidence: 89%
“…For example, SARS-CoV mainly binds to cells expressing angiotensin-converting enzyme 2 (ACE2), which is one of the major receptors of SARS-CoV when entering cells [11]. To date, more studies have confirmed that ACE2 is also the receptor of SARS-CoV-2 infection [4]; however, ACE2 displays high expression in the kidney, bile duct, and testis with low expression in the airways and lungs [12][13][14]. Lindskog, et al also emphasized that the expression of ACE2 in human respiratory system is limited, and questioned the role of ACE2 for infection in human lungs [15].…”
Section: Introductionmentioning
confidence: 99%
“…In December 2019, a novel pneumonia coronavirus, recently named Coronavirus Disease 2019 (COVID- 19) by World Health Organization (WHO), was first detected in several patients in Wuhan, China.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] The esophagus, large intestine (ileum and colon), and pancreas were identified as high-risk organs in the digestive system by the following papers. [16][17][18][19] The kidney and bladder as major organs of urinary system were also indicated to be high ACE2-expressed. 17,20,21 Besides, the testes and uterus were manifested to be susceptible organs, implying that the reproductive system was a potential route of viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…Single-cell RNA (scRNA) profiling is a state-of-the-art tool to dissect gene expression at single cell level, therefore was employed to explore the target cells of the SARS-CoV-2. Based on the profiling of ACE2 mRNA expression in different tissues/organs, multiple types of cells were proposed to be potentially targeted by SARS-CoV-2 virus, including the lung alveolar type 2 (AT2) cells [18], nasal epithelial cells [19], esophageal epithelial cells and intestinal enterocytes [20], liver cholangiocytes [21], cardiomyocytes [22], kidney proximal tubule cells [23], spermatogonia and Leydig/sertoli cells in testis [24]. However, unparallel to the many potential targets cells and organs proposed, the COVID-19 patients primarily displayed typical symptoms of inflammation in lung, where only a very small portion of cells (~0.64% of total cells, and ~1.4% of AT2 cells) expressed ACE2 mRNA [18]; meanwhile, the injuries in other organs/tissues, such as kidney and the intestinal track where ACE2 RNA expressed at high levels, seemed to be uncommon [1,25].…”
Section: Introductionmentioning
confidence: 99%